Tailoring the Edge Sites of 2D Pd Nanostructures with Different Fractal Dimensions for Enhanced Electrocatalytic Performance. Issue 8 (10th June 2018) - Yan, Yucong; Li, Xiao; Tang, Min; Zhong, Hao; Huang, Jingbo; Bian, Ting; Jiang, Yi; Han, Yu; Zhang, Hui; Yang, Deren
Abstract: The important role of edge sites in atomically thin 2D materials serving as catalysts is already of concerned in plenty of material systems and catalytic reactions, whereas comprehensive study of the edge sites in 2D noble‐metal nanocatalysts is still lacking. Herein, for the first time, a controllable etching approach to tailor the fractal dimensions and edge sites of Pd nanosheets is developed and the edge sites in these 2D nanostructures from both structural and chemical aspects are investigated. The as‐tailored 2D Pd nanostructures with extra edge sites exhibit substantially enhanced electrocatalytic performance for the formic acid oxidation reaction (FAOR). Moreover, careful analysis of the results from electrocatalytic measurements reveals that the specific activities for the edge sites in the 2D nanostructures far exceed the activities for the low‐index planes of Pd and even dominate the overall activity exhibited by the 2D noble‐metal catalysts. Abstract : Pd 2D nanostructures containing different types of edge sites are synthesized through etching Pd nanosheets in a controllable way. The edge sites in the Pd 2D nanostructures are more active and stable toward formic acid oxidation reaction compared to the low‐index planes of Pd and commercial Pd black catalysts.